A feasibility randomised controlled trial of ESCAPE-pain programme among patients with knee osteoarthritis in Malaysia - Che Hasan, Muhammad Kamil; Stanmore, Emma; Todd, Chris (2018)
Background: In Malaysia, around one in ten older people are diagnosed with osteoarthritis (OA). The most common form is knee OA. This can lead to functional limitations, impaired activities of daily living, reduced quality-of-life and increased risk of falls. Our systematic review of the literature concludes that a programme integrating exercise, education and active coping strategies (Enabling Self-management and Coping with Arthritic Pain using Exercise (ESCAPE-pain)) provides the best evidence for implementation. Thus, this study aims to evaluate the feasibility of ESCAPE-pain programme among patients with knee OA in Malaysian healthcare context.